Die Entstehung der europäischen Geldmärkte auf Grund der jüngsten Fugger-Forschungen von Götz von Pölnitz - Hanns Linhardt (Kredit und Kapital, 1970)
The Genesis of the European Money Markets in the Light of the Latest Research on the Fuggers by G. von Pölnitz The trading companies found in the upper German area since the 14th century were owned and managed by members of leading patrician families. The expansion of their international sphere of operations facilitated a shift from trade in commodities, with all its risks of procurement, sales, and ware housing and transport, to financial business with its facilities for transferring assets by way of bills of exchange and the giro system. Leading merchants like the Fuggers in Augsburg, who accomplished such a transition, imposed on the owners and employees a strict regime of internal orderliness and operating principles in the head office and their often numerous branches. By means of written articles of association, working regulations and inheritance arrangements they attained that internal consolidation (essentially secured by bookkeeping, inventories and balance sheets) which outwardly laid the foundation for the trust of numerous depositors and big debtors. Among the trading centres with their foreign agents and connections, the outstanding ones were those distinguished by visits from merchants from distant cities, the constant presence of their agents and the contact among creditors, debtors and financial intermediaries. In addition to the great northern Italian centres, they included the cities of Augsburg, Nuremberg, Lyons, Geneva and Antwerp. From the early 15th century onwards, under the influence of Anton Fugger, Augsburg moved more and more into the foremost ranks of such financial centres. The Fugger city attained international rank and repute. The more personal ties (like those between Anton Fugger and Emperor Charles V) were carried over into institutions like the trading company on the one hand and the imperial administration with its counsellors and notaries on the other, the more dependable was the progress made in the continuous process of objectivation of credit relationships, although that progress was not always undisturbed. The end of the process was marked by an institution which is indispensable for a modern commercial economy, the money and capital market. If we know its functions, we should also comprehend its conformation, to which great personalities made decisive contributions.
Keywords: 330